Franz Baermann Steiner a stranger in the world - Adler, Jeremy D. 1947-; Fardon, Richard 1952- (Berghahn Books, 2022)
Franz Baermann Steiner (1909-52) provided the vital link between the intellectual culture of central Europe and the Oxford Institute of Anthropology in its post-Second World War years. This book demonstrates his quiet influence within anthropology, which has extended from Mary Douglas to David Graeber, and how his remarkable poetry reflected profoundly on the slavery and murder of the Shoah, an event which he escaped from. Steiner's concerns including inter-disciplinarity, genre, refugees and exile, colonialism and violence, and the sources of European anthropology speak to contemporary concerns more directly now than at any time since his early death
Description based on online resource; title from PDF title page (publisher's Web site, viewed 04. Okt 2022)
Keywords: BIOGRAPHY & AUTOBIOGRAPHY / Social Scientists & Psychologists; Anthropologists -- England -- Biography; Anthropology -- Europe -- History -- 20th century; Jewish authors -- Biography; Poets -- Biography; Poets -- England -- Biography